2019
DOI: 10.1016/j.amepre.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Parent eReferral to Tobacco Quitline: A Pragmatic Randomized Trial in Pediatric Primary Care

Abstract: Introduction: Quitlines are effective in helping smokers quit, but pediatrician quitline referral rates are low, and few parents who smoke use the service. This study compared enrollment of parents who smoke in the quitline using electronic referral with that using manual referral. Study design: The study was designed as a pragmatic RCT. Setting/participants: Participants were recruited from one large, urban pediatric primary care site in Philadelphia, Pennsylvania with a high percentage of low-income families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Pediatric eReferrals were expected to increase after these inclusions, other studies by Jenssen et al have found that clinical decision support tools for parental tobacco treatment increased quitline enrollment. [37][38][39] Our finding that the hospital-based resident clinics had greater use of the eReferral order than faculty-based clinics may reflect a difference in patient or provider characteristics, residentphysician engagement, or promotional strategies. The hospitalbased clinic patient population may represent a different population as patients may reflect the urban, underserved neighborhood, or follow-up hospital discharges for patients that live remotely.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric eReferrals were expected to increase after these inclusions, other studies by Jenssen et al have found that clinical decision support tools for parental tobacco treatment increased quitline enrollment. [37][38][39] Our finding that the hospital-based resident clinics had greater use of the eReferral order than faculty-based clinics may reflect a difference in patient or provider characteristics, residentphysician engagement, or promotional strategies. The hospitalbased clinic patient population may represent a different population as patients may reflect the urban, underserved neighborhood, or follow-up hospital discharges for patients that live remotely.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers are the most invested entity in their own child’s well-being, and our work supports the time spent by pediatricians for TSE reduction by encouraging cessation contemplation and action [ 6 , 49 ]. Our work shows the value of promoting usage of traditional cessation aids (e.g., nicotine replacement therapies and advocacy of state quitline resources) [ 6 , 14 , 50 ]. Pediatricians are able to prescribe or assist in acquiring these therapies, which may be beneficial because an active prescriber-based approach can be superior to our study’s passive approach of solely advising participants to self-initiate contact with the state quitline for acquiring nicotine replacement therapy and behavioral counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Fax referral has been widely used to link patients who smoke with quitlines in healthcare settings; however, recent research indicates that quitline referral and use is enhanced by newly developed electronic health record−based referral methods (eReferral), which can increase quitline referrals 3-to 6-fold. 23,24 Moreover, eReferral systems, such as interoperable closed-loop feedback, return quitline treatment outcomes to referring healthcare systems and clinical personnel via electronic health record messages. 24−26 Such innovations more fully integrate quitline treatment with the patient's ongoing health care.…”
Section: Quitlines Todaymentioning
confidence: 99%
“…In addition, research shows that increasing the intensity or service provision of quitline treatment can meaningfully enhance effectiveness (e.g., using combination nicotinereplacement therapy instead of monotherapy increases long-term abstinence rates, 35 as does using 3 or more counseling calls versus fewer). 5,23 States, however, have frequently been forced to limit the comprehensiveness of their quitline services, including the number of counseling calls, typically because of budget constraints. 36 Quitline treatment pays high health and economic dividends to tobacco users, health insurers, and society at large.…”
Section: Quitlines Todaymentioning
confidence: 99%